Uganda : Third Review Under the Policy Support Instrument, Request for Waiver of Nonobservance of an Assessment Criterion, and Request for Modification of Assessment Criteria: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report ;, 2012)
This paper presents key findings of the Third Review for Uganda under the policy support instrument. Monetary policy has been tightened significantly to reduce core inflation, supported by a contractionary fiscal stance. All but one of the seven quantitative assessment criteria were met at end-June; most structural benchmarks were met, although several with delay. Tighter monetary and fiscal policies in the near term aim to reduce inflation rapidly, while medium-term policies strive to create fiscal space to support stepped-up public infrastructure investment.